Waste treatment in the metal manufacturing, forming, coating, and finishing industries - Wang, Lawrence K.; Shammas, Nazih K.; Hung, Yung-Tse (Advances in industrial and hazardous waste treatment series., 2009)
Comprehensive in its scope and directly applicable to daily waste management problems of specific industries, Waste Treatment in the Metal Manufacturing, Forming, Coating, and Finishing Industries covers hazardous industrial waste treatment, renovation, and reuse in the metal manufacturing, forming, coating, enameling, and finishing industries. It details specific hazardous and industrial wastes from metal industries, basic and advanced principals and applications, augmented by figures, tables, examples, and case histories. This book elucidates new industries a.